Violence and Threats of Violence Against Women and Men in the United States, 1994-1996 - Tjaden, Patricia ([Verlag nicht ermittelbar], 1999)
To further the understanding of violence against women, the National Institute of Justice (NIJ) and the National Center for Injury Prevention and Control (NCIPC), Centers for Disease Control and Prevention (CDC), jointly sponsored the National Violence Against Women (NVAW) Survey. To provide a context in which to place women's experiences, the NVAW Survey sampled both women and men. Completed interviews were obtained from 8,000 women and 8,005 men who were 18 years of age or older residing in households throughout the United States. The female version of the survey was fielded from November 1995 to May 1996. The male version of the survey was fielded during February to May 1996. Spanish versions of both the male and female surveys were fielded from April to May 1996. Respondents to the NVAW Survey were queried about (1) their general fear of violence and the ways in which they managed their fears, (2) emotional abuse they had experienced by marital and cohabitating partners, (3) physical assault they had experienced as children by adult caretakers, (4) physical assault they had experienced as adults by any type of perpetrator, (5) forcible rape or stalking they had experienced by any type of perpetrator, and (6) incidents of threatened violence they had experienced by any type of perpetrator. Respondents disclosing victimization were asked detailed questions about the characteristics and consequences of victimization as they experienced it, including injuries sustained and use of medical services. Incidents were recorded that had occurred at any time during the respondent's lifetime and also those that occurred within the 12 months prior to the interview. Data were gathered on both male-to-female and female-to-male intimate partner victimization as well as abuse by same-sex partners. Due to the sensitive nature of the survey, female respondents were interviewed by female interviewers. In order to test for possible bias caused by the gender of the interviewers when speaking to men, a split sample was used so that half of the male respondents had female interviewers and the other half had male interviewers. The questionnaires contained 14 sections, each covering a different topic, as follows. Section A: Respondents' fears of different types of violence, and behaviors they had adopted to accommodate those fears. Section B: Respondent demographics and household characteristics. Section C: The number of current and past marital and opposite-sex and same-sex cohabitating relationships of the respondent. Section D: Characteristics of the respondent's current relationship and the demographics and other characteristics of their spouse and/or partner. Section E: Power, control, and emotional abuse by each spouse or partner. Sections F through I: Screening for incidents of rape, physical assault, stalking, and threat victimization, respectively. Sections J through M: Detailed information on each incident of rape, physical assault, stalking, and threat victimization, respectively, reported by the respondent for each type of perpetrator identified in the victimization screening section. Section N: Violence in the respondent's current relationship, including steps taken because of violence in the relationship and whether the violent behavior had stopped. The section concluded with items to assess if the respondent had symptoms associated with post-traumatic stress disorder. Other variables in the data include interviewer gender, respondent gender, number of adult women and adult men in the household, number of different telephones in the household, and region code.